Interventions for people bereaved through suicide: systematic review. - McDaid, C; Trowman, R; Golder, S; Hawton, K; Sowden, A (2008)
BACKGROUND: Promoting the mental health of people bereaved through suicide is a key aim of the National Suicide Prevention Strategy. AIMS: To evaluate the effects of interventions to support people bereaved through suicide. METHOD: We conducted a systematic review of data from controlled studies of interventions for people bereaved through suicide. Studies were identified using systematic searches, the methodological quality of included studies was assessed and narrative synthesis conducted. RESULTS: Eight studies were identified. None was UK-based and all but one study had substantial methodological limitations. When compared with no intervention, there was evidence of some benefit from single studies of a cognitive-behavioural family intervention of four sessions with a psychiatric nurse; a psychologist-led 10-week bereavement group intervention for children; and 8-week group therapy for adults delivered by a mental health professional and volunteer. The findings from studies comparing two or more active interventions were more equivocal. CONCLUSIONS: Although there is evidence of some benefit from interventions for people bereaved by suicide, this is not robust. Further methodologically sound evidence is required to confirm whether interventions are helpful and, if so, for whom.